Can brand activism, when mediated by brand authenticity, generate brand love and brand advocacy? - Guiomar, Mariana Gonzaga Esteves Nunes (2023)
Traditionally, brands were positioned based on their performance characteristics. However, in competitive markets such as today's and with the characteristics of new consumers, this positioning is insufficient. The new generations have expectations of brands and businesses. They expect them to show concern and serve the community rather than focusing solely on the performance of their business. However, there is little literature validating the best way for brands to position themselves in this field and what effects it will have. This dissertation aims to fill this gap by examining the impact of brands becoming activists, mediated by authenticity and, in turn, how this relationship affects brand love and the creation of brand advocates. Based on an online survey grounded on articles by different authors, quantitative methodology was used to collect and analyse the data. The results indicate that although brand's identity and the clarity of its communication do not influence its authenticity, brands that have the ability to develop a commitment to social and political issues, and ensure that they do so authentically, will have a positive influence on their relationship with the consumer. This relationship can generate brand love, brand advocacy and brand recommendation, but also positively influence brand value and overall brand success.